Twentieth-Century British Political Facts, 1900-2000 - Butler, D. author. aut Link
XX, 584 p.
Keywords: Twentieth-Century British Political Facts is the definitive record of the who, the what and the when of British political history in the 1900s, providing reliable information which could not otherwise be found without many hours of digging in a library. Refined and updated since the seventh edition, this unique work has become as standard reference book for scholars, journalists, politicians, civil servants, students and all readers with an interest in political history.